Subtitle Analysis Using Oers’ Translation Strategies in Honkai: Star Rail Video Game - Basith, Rayhan Izzati; Al Ghifari, Muhammad Alfi (Universitas Teuku Umar, 2024)
Nowadays, video games interaction performed by the characters potentially offers the potential research analysing several forms of languages, including in the field of translation. Gacha Games, one of the most popular game providers serves the interesting plot and attractive story lines which involves many forms of communication. This study aims to identify the translation strategies from English to Indonesian of playable characters' responses in planet Jarilo-VI on a video game called Honkai: Star Rail version 2.2.0 by Gacha Games. In determining the translation of ten characters' reactions, the researcher applied a qualitative descriptive method by using Van Oers' selected translation strategies for video games. The research results show that only ten of the thirteen strategies were found: Contextualisation (26.79%), Regional Expression (6.22%), Transcreation (2.39%), Description (5.50%), Core translation (0.72%), Omission (11.24%), Borrowing (41.87%), Calque (1.44%), Literal translation (3.35%), and Adaptation (0.48%). From 13 translation strategies, borrowing was popularly used in analysing the subtitle. It indicated that most of subtitle used in video games tended to provide several meanings of special terms used in the game. Borrowing strategies made the researcher could not easily translate the special terms into the target language.